APLIKASI WEB SERVICE UNTUK MEMBERIKAN LAYANAN ACARA KAJIAN ISLAM DI INDONESIA (Information Technology and Telematics, 2014)
Abstract-- Islamic studies Events which provide knowledge to the people about the teachings of Islam are now often implemented. To provide information about the existence of the event, organizers uploaded on his personal website, so visitors should visit the site belongs to the committee one by one.While web developers who want to take the data to do the copying information manually.This can be overcome by creating a system that can accommodate information from event organizers and can be used to show information to visitors. The system should also have a function that allows developers to retrieve data from the information uploaded by the committee.The system will be built with PHP, MySQL and XML. The system is made to display a list of event studies, detailed studies, new studies add events, search for reviews based on the theme, speakers, province. The system can also perform event management studies by changing or deleting data and also provided a web service. As for web services that can be used by web developers, which will be used is a REST web service. By using the GET method in REST web service, the data in the system will be converted into an XML format in a unique URL address. In this study, developers are only required to enter  he parameters and the system will display the data according to the parameters entered by the user in XML format.Keyword-- Web Services, XML , REST, GET, IslamicStudies Event